How to survive and prosper as an artist selling yourself without selling your soul - Michels, Caroll (New York Allworth Press, 2018)
An acclaimed guide, empowers artists to take control of their careers to create a fulfilling life and earn a decent income.

In this newly revised edition, Caroll Michels continues to demystify the inner workings of the art world and challenge the status quo. New chapters discuss such topics as: New business models for artists: Going to the extreme; the use of social media and website development as marketing and publicity tools and what does and doesn't work; the confusion between the “art-buying public” and the “general public” and their differences; new suggestions for establishing and calculating prices for artwork; neighborhood gentrification and the growing challenges of securing a reasonably priced live/work space; how dealers find artists, how to negotiate with dealers, and how to understand a dealer's agenda.

Using her own experiences as an artist as well as the experiences of her clients, Michels crafts a must-read guidebook for anyone interested in embarking upon a successful career as an artist.
Includes bibliographical references and index.
Keywords: Art -- Marketing; Art -- Vocational guidance -- United States